Outcome analysis of intercondylar humerus fractures treated by locking compression plates - Vipendra Singh; Suresh Uikey; Ajit Ganvir; Deepak S. Maravi; Sanjiv Gaur (International Journal of Medical Research and Review, 2016)
Background: Distal humeral fractures are uncommon fractures. They occur in both younger as well as older patients. The complex shape of the elbow joint, the adjacent neurovascular structures, the sparse soft tissue cover combine to make treatment difficult. Previous methods of conservative treatment have caused significant functional impairment. Thus the consensus has shifted towards treatment with open reduction and internal fixation so as to provide stability and early mobilization. Different modalities like 1/3rd tubular plate, reconstruction plate, K wires, double tension band wiring have been tried. The quality of elbow function following the treatment is related to the degree to which the normal anatomic relationships are restored.Materials and Methods: 27 patients of Intercondylar Humerus fractures classified by Riseborough & Radin system and treated by ORIF by pre-contoured AO Locking compression plates. Clinical and radiological follow-up performed and patients assessed for pain, range of motion, and Mayo elbow performance score.Results: Average follow up was of 6 months. Average age was 37.5 years (18-62 years). Fracture consolidation observed at an average of 12.8 weeks (10-14 weeks). The outcome was excellent or good in 17 patients. 3 patients had infection, 1 case each of ulnar neuropathy, mal-union and myositis ossificans. There were no cases of implant migration, secondary displacement or implant failure.Conclusion: Anatomically pre-shaped distal humerus locking plate system is useful in providing stable fixation for complex distal articular fracture and facilitating early postoperative rehabilitation. The low rate of implant failure in the present study indicates that the technique is promising.